Modelagem da dispersão de odores em ambientes urbanos - Dourado, Harerton Oliveira (2013)
The present work investigated odour dispersion modelling in the presence of obstacles (cubical and complex-shaped buildings) under neutral atmospheric conditions employing numerical modelling based on the transport equations (CFD8) as well as on algebraic Gaussian- based models (AERMOD9, CALPUFF10 and FPM11) and using field and wind tunnel data to validate the models results and evaluate the models performance. To include atmospheric turbulence effects on dispersion, two different subgrid scale models associated to the Large Eddy Simulation (LES) technique were investigated (Dynamic Smagorinsk and WALE12) and to include the building effects on dispersion in the Gaussian-based models, PRIME13 was used. The use of PRIME was also proposed for FPM as a novelty. Overall, results indicate the use of the CFD/LES might be a useful tool for assessment of odour dispersion and impact in the presence of obstacles and also for the development of Gaussian models. Results also indicate that the proposed FPM, which included the effects of the obstacle based on the PRIME model, is a very useful tool in odour dispersion modelling, due to its simplicity and easy set up if compared to the more complex CFD modelling and even regulatory models AERMOD and CALPUFF. The great advantage of FPM is the possibility of estimating intermittency and also the peak-to-mean (P/M) concentration ratio, which are useful parameters for odour impact assessment. Results obtained in the present work indicate the determination of the plume segments dispersion parameters, as well as the long term dispersion parameters in the near field of the source and obstacle in FPM might be improved and CFD could be used as development tool for this purpose. Key words: Odour control, dispersion, computational fluid dynamics (CFD), mathematical modelling, fluctuating plume Gaussian modelling, Large Eddy Simulation (LES).